PENGARUH DIRECT SELLING DAN MEDIA SOSIAL MELALUI FACEBOOK TERHADAP MINAT BELI KONSUMEN PADA ROKOK SIN HERBAL - Firona, Warham; Iskandar, Donant Alananto (Economic Faculty, Attahiriyah Islamic University, 2018)
This study aims to determine whether there is influence between direct selling and social media through facebook to consumer buying interest in cigarettes sin herbs in Pesona Anggrek, Bekasi Utara. This study used an associative quantitative approach through a survey to 60 members. Sampling method is probability sampling by using simple random sampling. Hypothesis test results (t test) showed that the variables of direct selling and social media through facebook have a significant effect on buying interest. This is indicated by the absolute t value of direct selling and social media through facebook both bigger than t table that is equal to 2.002. The conclusion of this research that direct selling and social media through facebook each have an effect on buying interest. This can mean that, declining and increasing buying interest depends on how to apply direct selling system and social media through facebook effectively. Keywords: Direct selling, social media through facebook, buying interest,